Inhibiting RIP1 Improves Chronic Stress-Induced Cognitive Impairments in D-Galactose-Induced Aging Mice - Qing, Wenxiang; Li, Fan; Wang, Xueqin; Quan, Chengxuan; Ouyang, Wen; Liao, Qin (Frontiers in Behavioral Neuroscience, 2018)
Mounting evidence shows that chronic stress can affect both the structure and function of the brain resulting in decreased synaptic plasticity and cognitive dysfunction. Although several studies have indicated that aged brains are more vulnerable to chronic stress, it remains unknown how to prevent stress-induced memory deficits in aged animals. Neuroinflammation plays an important role in the pathogenesis of chronic stress-related brain dysfunction. Receptor-interacting protein 1(RIP1) is a key molecule that can modulate inflammation, apoptosis, and necroptosis. Here, we investigated whether inhibiting RIP1 using necrostatin-1 during chronic stress could improve chronic stress-related brain dysfunction in D-galactose-induced aging mice. The stressed mice underwent restraint stress for 14 days. Necrostatin-1 (6.25 mg/kg) or vehicle was administered intraperitoneally once every 3 days during the stress period. Locomotor activity was tested using the open field test and cognitive function was assessed using the novel object recognition and Barnes maze tests. The hippocampus was collected to assess neuroinflammation (Iba1, IL-1α, IL-1β, TNF-α, and C1q), necroptosis (RIP1, RIP3, mixed lineage kinase like [MLKL], and NF-κB), neuroplasticity (doublecortin, NR1, NR2A, NR2B, GluA1, and GluA2), and the expression of glucocorticoid and mineralocorticoid receptors. Blood samples were collected to quantify the levels of corticosterone. We found that chronic stress induced obvious memory impairment and neuroinflammation, decreased neurogenesis and GluA2 expression, and increased the expression of RIP1 and NF-κB. Inhibiting RIP1 by necrostatin-1 during chronic stress rescued the memory impairment and alleviated the pathological changes induced by stress. These suggest that inhibiting RIP1 using necrostatin-1 improves chronic stress-related brain dysfunction in D-galactose-induced aging mice. The potential mechanisms include limitation of neuroinflammation and the rescue of neurogenesis and GluA2 expression.